Health literacy in individuals with knee pain-a mixed methods study - Charlotte Sylwander; Astrid Klopstad Wahl; Maria L.E Andersson; Emma Haglund; Ingrid Larsson (BMC, 2023)
Abstract Background Low health literacy is associated with worse pain and poorer self-management. This study (1) examined the level of health literacy and associations with lifestyle habits, health status, chronic pain, and radiographic knee osteoarthritis; and (2) explored experiences illuminating health literacy among individuals with knee pain. Methods A convergent parallel mixed-methods design was used, including 221 individuals. Health literacy was assessed by HLS-EU-Q16 and eHEALS. The questionnaire included questions on lifestyle habits, health status, and pain distribution. Radiographic knee osteoarthritis was assessed with x-rays. Associations were analysed using logistic regression analyses. Individual semi-structured interviews were conducted (n = 19) and analysed with qualitative content analysis. Results The result showed that 71% reported sufficient health literacy. Higher education, healthy lifestyle habits, better general health, and absence of widespread pain were associated with sufficient health literacy. Experiences regarding health literacy influencing the decision-making process toward a decision on action comprised: (1) searching for information actively or passively; (2) processing of the information included being informed, critical, and interpretive; and (3) taking a stand on the information based on trustfulness and motivation. Conclusion Seven out of 10 reported sufficient health literacy. Despite this, unhealthy lifestyles were common, suggesting that having sufficient HL is not enough for a behavioural change and the decision-making process, including different phases such as searching, processing, and taking a stand on health information is important to consider. More research on health literacy is needed to gain knowledge of how best to develop health promotion in individuals with knee pain.